Management Strategies of Japanese Language Training at LPK Yaruki Lubuk Alung Padang Pariaman Regency - Ermaini, Septia Dwi; Natsir, MHD (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This study aims to identify the management strategies of Japanese language training at LPK Yaruki Lubuk Alung in preparing participants for internship and employment programs in Japan. The research employed a qualitative method with a case study approach. The study was conducted at LPK Yaruki Lubuk Alung, located on Jalan Irigasi, Kampung Ladang, Sungai Abang, Lubuk Alung, Padang Pariaman Regency, West Sumatra. Data were collected through interviews, observations, and documentation. Data analysis was carried out through the processes of data reduction, data display, and conclusion drawing. The data sources in this study consisted of the research subject and informants, where the research subject was the manager or director, while the informants were managers, instructors, and training participants. The findings revealed that the management strategies of the training were implemented through seven management functions, namely planning, organizing, staffing, directing, coordinating, reporting, and budgeting. These strategies have proven to support the effectiveness of the training and the participants’ success in obtaining the JLPT N4 certificate as well as their readiness to work in Japan.